A prevalent and culturable microbiota links ecological balance to clinical stability of the human lung after transplantation - Sudip Das (Nature Portfolio, 2021)
Here, the authors combine 16 S rRNA sequencing, culture and bioinformatics to profile the microbiome in 234 serial bronchoalveolar lavage samples from 64 lung transplant recipients collected over 49-months and identify distinct compositional states, termed pneumotypes, linked to current health status, and establish a collection of primary lung bacterial isolates, LuMiCol.